Security Alliances in the Indo-Pacific: Examining Their Effectiveness in Addressing the Security Threats - Zulafqar Ahmed; Ngoma Mushinda Betao (Indonesian Scientific Publication, 2026)
The Indo-Pacific has become the primary arena of twenty-first century strategic competition, yet the comparative effectiveness of its regional security alliances remains underexplored. This study evaluates the effectiveness of major alliances and strategic partnerships — particularly the Quad and AUKUS — in responding to contemporary regional security challenges, using a qualitative comparative case study approach drawing on official policy documents, strategic reports, and academic literature. The findings reveal that these alliances have strengthened maritime domain awareness, military interoperability, intelligence sharing, and conventional deterrence. However, their effectiveness is constrained by divergent national strategic priorities, uneven institutional commitment, limited collective enforcement mechanisms, and concerns over regional inclusivity. While cooperation in maritime security, cybersecurity, and humanitarian assistance has grown, coordinated responses to grey-zone activities, economic coercion, and broader strategic competition remain limited. The study concludes that future Indo-Pacific security architecture must prioritize stronger policy coordination, institutional flexibility, and inclusive multilateral cooperation to effectively address the region's evolving security environment.